Educational Performance Management Model for Higher Education: Soft System Methodology Based Action Research Approach - Habibullah Jimad; Yuningsih Yuningsih; Nova Mardina; Ryzal Perdana (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Educational staff is one of the main elements that determine the success of higher education. One of the factors that affect the performance of educational staff is a performance reward in the form of remuneration. The purpose of this study is to build a performance management model for educational staff at the State University Public Service Agency (SUPSA). The approach used Soft System Methodology and the Analytic Hierarchy Process. The samples in this study were educational staff at the State University Public Service Agency in Lampung Province. Based on the results of the SSM, it shows that many parties have an interest in the performance of education personnel, namely lecturers, students, unit leaders, the Chancellor, as well as the Ministry of Education and Culture and the Ministry of Finance. The AHP results indicate that the priority of the education staff performance strategy is based on competence and performance measurement. The limitation of this research is that the SSM stage is carried out only in the sixth stage of the seven stages. It is also necessary to conduct a study on activity mapping and business process preparation as part of the development of a performance management application system for education personnel.